Effect of Baduanjin exercise on cerebral blood flow and cognitive frailty in the community older adults with cognitive frailty: A randomized controlled trial - Huiying Lin; Yu Ye; Mingyue Wan; Pingting Qiu; Rui Xia; Guohua Zheng (Elsevier, 2023)
Background/Objectives: Regular Baduanjin exercise training has been shown to be beneficial to the physical and cognitive health of older adults, but the underlying mechanisms remain to be investigated. This study examined the influence of Baduanjin on cerebral hemodynamics in community-dwelling older adults with cognitive frailty. Design: Randomized controlled trial. Methods: A total of 102 eligible participants were randomly allocated into the Baduanjin exercise intervention group (BEG) or usual physical activity control group (CG) for 24 weeks. Cerebral hemodynamic parameters of bilateral middle/anterior cerebral artery and basilar artery, cognitive ability and physical frailty were assessed using Transcranial Doppler (TCD), Montreal Cognitive Assessment (MoCA) and Edmonton Frailty Scale (EFS) at baseline and 24 weeks post-intervention. Results: After 24 weeks intervention, the changes in peak systolic velocity (PSV), mean blood flow velocity (MBFV), and end diastolic velocity (EDV) in the right middle cerebral artery and basilar artery were better in the BEG than in the CG; the increase in MoCA scores and the decrease in EFS scores were significantly higher in the BEG than in the CG. Moreover, the interaction of exercise and time on those variables showed obvious significance. Conclusions: The 24 weeks Baduanjin exercise training had a positive beneficial effect on cerebral blood flow in community-dwelling older adults with cognitive frailty. This may be a potential mechanism by which Baduanjin exercise improves the cognitive frailty in older adults. Trial registration: Chinese Clinical Trial Registry, ChiCTR1800020341. Date of registration: December 25, 2018, http://www.chictr.org.cn/showproj.aspx?proj=29846.